Pengaruh Sustained Silent Reading Terhadap Motivasi Membaca, Pengetahuan Kosakata, dan Pemahaman Membaca Teks Bahasa Inggris Siswa Kelas 1E Sekolah Dasar Swasta X di Jakarta Barat [Effect of Sustained Silent Reading to Reading Motivation, Vocabulary Knowledge, and Reading Comprehension of Elementary School X Grade 1 Students in West Jakarta] - Cheriebelle, Cheriebelle; Markus, I Made (Jurnal Teropong Pendidikan, 2022)
Sustained Silent Reading (SSR) is a reading method with a purpose to increase enjoyment in reading. The enjoyment in reading will improve the reading skills which lead to increased reading motivation, vocabulary knowledge, and reading comprehension. This research was conducted to know the effect of SSR to grade 1 students’ reading motivation, vocabulary knowledge, and reading comprehension as young learners. The research design used a quantitative, pre-experimental one group pretest and posttest method. 24 students of 1E class of Elementary School X who received the SSR treatment are the subjects of this research. To collect the data, the researcher did a literature review and used instruments such as reading motivation questionnaire which is adapted from MRQ and RAI (Wigfield & Guthrie, 1997), vocabulary and reading comprehension tests. The data were analyzed using SPSS v. 21 software, with descriptive and inferential statistics (Paired Sample t-test and Wilcoxon Signed Ranks). After the treatments, there were increment in the students’ reading motivation (t = 4.881; ρ = 0.000), vocabulary knowledge (Z = -2.453; ρ = 0.014), and reading comprehension (Z = -3.539; ρ = 0.000). These analyses showed that the SSR method brought improvements to the students’ reading motivation, vocabulary knowledge, and reading comprehension.